If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11 + 6 + 7n + -9n = n + 1 Combine like terms: -11 + 6 = -5 -5 + 7n + -9n = n + 1 Combine like terms: 7n + -9n = -2n -5 + -2n = n + 1 Reorder the terms: -5 + -2n = 1 + n Solving -5 + -2n = 1 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -5 + -2n + -1n = 1 + n + -1n Combine like terms: -2n + -1n = -3n -5 + -3n = 1 + n + -1n Combine like terms: n + -1n = 0 -5 + -3n = 1 + 0 -5 + -3n = 1 Add '5' to each side of the equation. -5 + 5 + -3n = 1 + 5 Combine like terms: -5 + 5 = 0 0 + -3n = 1 + 5 -3n = 1 + 5 Combine like terms: 1 + 5 = 6 -3n = 6 Divide each side by '-3'. n = -2 Simplifying n = -2
| 4x-2(5x-8)=-56 | | (6x)=6(xy) | | 2m^2-7m-7m-13=-10 | | 5w-5+2(3w+7)=-5(w+1) | | 15u-8u=49 | | 6=4x/(12-x) | | X-2(-.3)=2 | | 13=5x+11 | | 3n+2=3 | | 3(2+2y)+4y=3 | | 7+4q=11+34 | | 6+6x=6(x-5) | | 7(x+4)=-2(5x-5)+2x | | (2x+1)-(-4x-9)= | | x+3x+6x=3450 | | 12(10)+3(14)=162 | | 9-x=x+12 | | 7-2n=4 | | 8(10)+3(14)=122 | | 4z-5=8x+3 | | -3(-2w+3)-9w=3(w-7)-3 | | 2y(y)=400 | | 2.1x-12.2= | | 481.194=13.4*6.3*w | | 3x-4+2x+10=21 | | -12/5=-6u | | -3(2x-4)=5x | | 3x+7-9+x=2x+3-x+4 | | -21=7/8y | | -6=-3/5w | | X+Y-3Z= | | (x^5)^(9/5) |